Frontiers of labor : comparative histories of the United States and Australia - Patmore, Greg; Stromquist, Shelton, 1943- (The working class in american history, 2018)
Alike in many aspects of their histories, Australia and the United States diverge in striking ways when it comes to their working classes, labour relations, and politics. Greg Patmore and Shelton Stromquist curate innovative essays that use transnational and comparative analysis to explore the two nations' differences. The contributors examine five major areas: World War I's impact on labor and socialist movements; the history of coerced labour; patterns of ethnic and class identification; forms of working-class collective action; and the struggles related to trade union democracy and independent working-class politics. Throughout, many essays highlight how hard-won transnational ties allowed Australians and Americans to influence each other's trade union and political cultures.